Strategi Pengembangan Kewirausahaan Sosial PT Bina Swadaya Konsultan - Ikhwan Safa'at; Rizal Syarief; Ani Suryani (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2014)
In the second World Entrepreneurship Forum in Lyon, France in 2009, Bina Swadaya stated definition of Social Entrepreneurship is social development with entrepreneurship solution. Developments that includes aspects of poverty alleviation, productive employment and social integration. PT Bina Swadaya Konsultan, a subsidiary of Bina Swadaya Organization with the spirit of entrepreneurship in an effort to sustain the community development process that can provide benefits for society and the life-cycle companies develop social entrepreneurship in accordance with its competence. .  The purpose of this study was (1) Identify the internal and external factors that influence the development of social entrepreneurship PT BSK, (2) Getting some alternatives strategy in the development of social entrepreneurship to the purpose of the development of social entrepreneurship, (3) Obtain the priority of social entrepreneurship development strategy in accordance with the company's internal and external conditions. Research methodology using IFE, EFE, IE Matrix, SWOT and QSPM. Priority strategy of development of social entrepreneurship PT BSK are (1) Restructuring and Market Penetration, (2) Focus, Product Development and Differensiation, (3) Market Development and Market Penetration, (4) Vertical Integration, (5) Product Improvement and Diversification.